A Novel Polysaccharide from Sargassum weizhouense: Extraction Optimization, Structural Characterization, Antiviral and Antioxidant Effects - Yi Zhao; Jiaji Chen; Yiqu Ding; Mengyuan Luo; Yanmei Tong; Tingjun Hu; Yingyi Wei (Antioxidants, 2023)
Porcine reproductive and respiratory syndrome virus (PRRSV) is one of the most economically important pathogens in the global swine industry over the past three decades. There is no licensed antiviral medication that can effectively control this infection. In the present study, the structure of SP-1 isolated and purified from Sargassum weizhouense was analyzed, and its antioxidant capacity and antiviral effect in MARC-145 cells against PRRSV were investigated. The results showed that SP-1 is a novel polysaccharide which mainly is composed of →4)-β-D-ManpA-(1→, →4)-α-L-GulpA-(1→ and a small amount of →4)-β-D-GalpA-(1→. PRRSV adsorption, replication, and release were all suppressed by SP-1. SP-1 therapy down-regulated mRNA expression of the CD163 receptor while increasing the antioxidant gene expression of Nrf2, TXNIP, and HO-1; increasing the protein expression of NQO1 and HO-1; and drastically reducing the protein expression of p-p65. The findings indicated that SP-1 reduces PRRSV adsorption, replication, and release through blocking the expression of the crucial CD163 receptor during infection. Meanwhile, SP-1 exerts antioxidant effects in PRRSV-infected cells through the activation of the Nrf2-HO1 signaling pathway.